Influence of Fresh Fm "Kekere Akin" on the academic performance of primary school pupils in Osogbo, Osun State. (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This work examines the influence of radio educational programme on the Academic Performance of Primary School Pupils, focusing on the "Kekere Akin" programme broadcast by Fresh FM in Osogbo, Osun State, Nigeria. Through a thorough survey of pupils of both private and public schools in Osogbo, the study investigates the correlation between exposure to radio educational programmes and students' academic performance. It was discovered that primary school pupils are highly engaged with the "Kekere Akin" radio program, with over half listening every Sunday. The program is perceived as fun and engaging, attracting students who appreciate learning new things. The program has a positive impact on students' academic performance, particularly in key subjects like Mathematics, Yoruba language, and Social Studies. Factors influencing the relationship between exposure to the program and academic performance include access to a radio at home and parental support. However, barriers such as limited access to radio devices, programme quality, inclusivity, and parental involvement were identified as key factors influencing the effectiveness of these programmes. Recommendations include enhancing programme quality, addressing access barriers, promoting inclusivity, strengthening parental engagement. By addressing these considerations, educational broadcasters can harness the power of radio to foster learning and academic achievement among primary school pupils, thereby contributing to the advancement of primary education